DOI: 10.22215/etd/2013-07273
|View full text |Cite
|
Sign up to set email alerts
|

Hygrothermal properties of cross laminated timber and moisture response of wood at high relative humidity

Abstract: A Thesis submitted to the Faculty o f Graduate and Postdoctoral Affairs in partial fulfillment o f the requirements for the degree o f Master o f Applied Science in Civil and Environmental Engineering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The adhesive layer (assumed to extend 2 mm deep in the plank) was modeled with the same material properties as spruce, with the exception that the water vapor permeability and liquid water diffusivity were decreased by 50%. This was in line with the results obtained in [16] which showed that CLT's vapor permeability and moisture diffusivity are substantially reduced in comparison with those of solid wood.…”
Section: Wall Assembliessupporting
confidence: 92%
See 2 more Smart Citations
“…The adhesive layer (assumed to extend 2 mm deep in the plank) was modeled with the same material properties as spruce, with the exception that the water vapor permeability and liquid water diffusivity were decreased by 50%. This was in line with the results obtained in [16] which showed that CLT's vapor permeability and moisture diffusivity are substantially reduced in comparison with those of solid wood.…”
Section: Wall Assembliessupporting
confidence: 92%
“…Figure 2 shows the schematic of the wood frame and massive timber walls. Material properties of wall components were obtained from [15] and [16]. CLT panel is composed of wood (spruce) layers glued together with an adhesive.…”
Section: Wall Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CLT adhesive layer (assumed to extend 2 mm deep in the plank) was modeled with the same material properties as spruce, with the exception that the water vapor permeability and liquid water diffusivity were decreased by 50%. In fact, previous studies on the characterization of the hygrothermal properties of CLT have shown that its vapor permeability and moisture diffusivity are substantially reduced in comparison with those of solid wood [26].…”
Section: Building and Wall Componentsmentioning
confidence: 98%
“…There are different building systems used across the world and even if wood is a common material; it is used under various forms made from various species. Al Sayegh (2012) and Lepage (2012) showed that differences between CLTs from various origins (Europe and Canada) and the differences mainly came from the cracks in the wood and the way boards were glued together, this having an effect on the permeability of the panels. Ozolins et al (2013) evaluated hygrothermal properties of multi-layered walls in cold climate using COMSOL and WUFI and confirmed the results with in-situ measurements.…”
Section: Model Validationmentioning
confidence: 99%